CG-NAP/Kinase Interactions Fine-Tune T Cell Functions - Verma, Navin Kumar; Chalasani, Madhavi Latha Somaraju; Scott, John D.; Kelleher, Dermot (Frontiers in Immunology, 2019)
CG-NAP, also known as AKAP450, is an anchoring/adaptor protein that streamlines signal transduction in various cell types by localizing signaling proteins and enzymes with their substrates. Great efforts are being devoted to elucidating functional roles of this protein and associated macromolecular signaling complex. Increasing understanding of pathways involved in regulating T lymphocytes suggests that CG-NAP can facilitate dynamic interactions between kinases and their substrates and thus fine-tune T cell motility and effector functions. As a result, new binding partners of CG-NAP are continually being uncovered. Here, we review recent advances in CG-NAP research, focusing on its interactions with kinases in T cells with an emphasis on the possible role of this anchoring protein as a target for therapeutic intervention in immune-mediated diseases.